Scour Technology : - Annandale, G. W. (McGraw-Hill, 2006)
Structures built in or near rivers and other channels can be vulnerable to scour around their foundations. If the depth of the scour becomes significant, the stability of the foundations may be endangered, with a consequent risk of damage or failure of the structure. There have been several bridge failures, resulting in transport disruption, economic loss and, on occasion, loss of life. The factors influencing scour are complex and vary according to the type of structure. Protection for preventing scour needs to be designed to withstand the flow forces imposed on them and have to be practical to build and install, while minimizing adverse environmental effects. This book covers the entire Scour Technology area and is prepared by one of the leading experts on the subject